First-principles computation of magnesium doped CaZrO3 perovskite: A study of phase transformation, bandgap engineering and optical response for optoelectronic applications. (June 2020) - Zeba, I.; Ramzan, M.; Ahmad, Riaz; Shakil, M.; Rizwan, M.; Rafique, M.; Sarfraz, M.; Ajmal, M.; Gillani, S.S.A.
Abstract: In the present work the structural, electronic and optical properties of pure CaZrO3 have been tuned by the magnesium (Mg) doping concentrations (1.41%, 2.82% and 4.23%) by first-principles computation, based on the density functional theory (DFT), implemented within the CASTEP code with Perdew-Burke-Ernzerhof-Generalized-Gradient-Approximations (PBE-GGA) exchange correlation functional and USP (ultra-soft pseudo-potential). From structural results optimized lattice parameters and unit cell volume are obtained, well in match with literature, and with 4.23% doping concentration of Mg structural phase transformation, cubic to pseudo-cubic tetragonal, along with a noticeable influence on electronic band gap squeezing, with the appearance of new k -symmetry points at Brillouin zone, is observed. Electronic band structure shows that with, 1.41% and 2.82% doping concentration of Mg, the indirect band gap of host changes to direct one while with 4.23% doping concentration it remains same and value of host band gap is reduced from 3.279eV to 2.189eV. The phase transformation and reduction of band gap is explained with partial and total density of sates and have great influence on the optical properties. Analysis of optical properties with Mg doping reveals that the absorption edges of the doped CaZrO3 show the red shift (1.9eV–0.65eV) whereas the static refractive index almost remain same. Electron energy loss spectra is observed to be consistent with absorption spectra. The doping of Mg concentration changes positively in electronic and optical properties and it would be very potential candidate for optoelectronic applications. Highlights: A comprehensive study of influence of Mg doping concentrations on structural modification, bandgap engineering and optical response of CaZrO3 . The inclusion of Mg doping concentrations at Ca site in CaZrO3 alter the band gap from 3.279eV to 2.189eV. With 4.23% Mg doping concentration, structural phase transformation from cubic to pseudo-cubic tetragonal occurs. The absorption edge shifted to lower energy with Mg doping. Electronic structure and optical properties are strongly correlated.